Enfermedad del hígado graso asociada a la disfunción metabólica como factor de riesgo para ictus isquémico en pacientes atendidos en el Hospital Regional Docente de Trujillo 2019 - 2021 - Mercado García, Kenyi Jean Pierre (2022)
Ischemic stroke (CVA) is a disease that compromises both adults and older adults, maintaining a constant prevalence and incidence in the population; leading to a poor quality of life due to the multiple complications that this entails, therefore, it is necessary to timely identify those factors related to its appearance, such as arterial hypertension or type 2 diabetes mellitus, however little is known about the association with fatty liver disease associated with metabolic dysfunction (previously called non-alcoholic fatty liver disease), this being a disease that is increasing in prevalence in the population due to excessive consumption of carbohydrates and saturated fats together with little daily physical activity (sedentary lifestyle). The presence of these factors makes it increasingly feasible to show more cases of people with ischemic stroke. Objetive: To determine if fatty liver disease associated with metabolic dysfunction is a risk factor for ischemic stroke in patients treated at the Hospital Regional Docente de Trujillo. Materials and Methods: An analytical, observational, retrospective case-control study will be carried out, consisting of the clinical history of each patient treated in the Internal Medicine and Neurology Service of the Hospital Regional Docente de Trujillo during the period 2019-2021 who meet the criteria of selection. A simple random sampling will be carried out by groups